1965
DOI: 10.1126/science.147.3659.738
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Studies of Living Muscle

Abstract: Measurements of nuclear magnetic relaxation times for protons of water in living skeletal frog muscle show the transverse relaxation time, T(2), increases when a muscle contracts isometrically. This result and other experimental data suggest that a fraction of the intracellular water molecules have restricted rotational freedom and that this fraction decreases when contraction occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
59
2

Year Published

1970
1970
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(67 citation statements)
references
References 12 publications
6
59
2
Order By: Relevance
“…The assumptions made in this paper are in accord with results of nuclear magnetic resonance measurements that indicate a reduced freedom of motion of water in muscle and an increase in freedom in contraction (9)(10)(11)(12). The theory is also in accord with my contention that muscle contraction is "contraction," that is, the shortening of elongated particles, fibers.…”
supporting
confidence: 77%
“…The assumptions made in this paper are in accord with results of nuclear magnetic resonance measurements that indicate a reduced freedom of motion of water in muscle and an increase in freedom in contraction (9)(10)(11)(12). The theory is also in accord with my contention that muscle contraction is "contraction," that is, the shortening of elongated particles, fibers.…”
supporting
confidence: 77%
“…In particular, signal intensity changes due to increases in the relaxation time (T2) of tissue water can be measured to indicate exercise-induced activity of muscles. 40 This phenomenon was originally described in 1965, when Bratton et al 8 reported an increase in the T2 of isolated frog skeletal muscle following stimulated isometric contractions. Subsequently, Fleckenstein et al 31 reported the first similar phenomenon in living human subjects and, as a consequence, Fisher et al 29 suggested that this prolongation in T2 relaxation time could be used as a quantitative measurement for muscle activity.…”
mentioning
confidence: 99%
“…Already in 1965, proton NMR relaxation times of living frog muscle were published [13], and in 1968 the first whole-body spectrum of a rat was taken [14]. In the 1960s and 1970s a very large amount of work was published on relaxation, diffusion, and chemical exchange of water in cells and tissues of all sorts.…”
Section: Resistive Electromagnets the Beginning Of Analytical Nmrmentioning
confidence: 99%